Kritik Ibn Al-‘Arabi Terhadap Aqidah Syiah Dalam Kitab al-'Awasim wa al-Qawasim - Muhammad Iqbal (UIN Mataram, 2022)
This article aims to analyze the methods used by Ibn ‘Arabi al-Ma’rifi in order to reject all the theological concepts of Shia, the second Islamic sect after Sunni based on his book al-‘Awasim wa al-Qawasim. This article used qualitative methods based on library research by reading the book of the author and analyse the methodological point of the author in his critics. The life of Imam Abu Bakr Ibn al-Arabi al-Ma’afari - may God have mercy on him - was full of knowledge since his childhood, as he grew up in a house of knowledge and righteousness, and his journey to the countries of the Orient had the greatest impact on his brilliance in the types of sciences and knowledge. With the breadth of his knowledge and the length of his sale, he is an investigator and an auditor. He is a Sunni scholar keen on the Book and the Sunnah. Imam Abu Bakr bin al-Arabi al-Ma’afari, may God have mercy on him, followed the method of Ahl al-Sunnah wal-Jamaa’ah in criticizing the beliefs of the Shiites. His clear position in responding to Ali's succession, may God be pleased with him, in the belief of the Shiites, and his eminent response, may God have mercy on him, to their suspicions about the Companions.